Retrieval of Distally Migrated Coils with Detachable Intracranial Stent during Coil Embolization of Cerebral Aneurysm - Singh, Devendra Pal (J Cerebrovasc Endovasc Neurosurg, 2016)
Migration of coils during endovascular procedures is a rare, but well-known complication. We are reporting two cases of successfully retrieving migrated coil using detachable intracranial stent. In both of our cases there was distal migration of coil during the intracranial aneurysm coiling procedure. The Solitaire® AB stent (Covidien, Irvine, CA, USA) was used to retrieve those coils. The stent was passed distal to the migrated coil using standard technique. It was then partially deployed and gradually withdrawn along with the entangled coil. Coil retrieval using the fully retrievable intracranial stent is a very simple, safe and easily available alternative for retrieval of distally migrated coil.